Interaction of gene polymorphisms in the risk of coronary artery disease and random amplified polymorphic DNA analysis of coronary artery disease - Chu, Wern Cui (2015)
Genetic variants of methylenetetrahydrofolate reductase (MTHFR), endothelial nitric oxide synthase (eNOS), and cholesteryl ester transfer protein (CETP), influence homocysteine,nitric oxide synthesis, and high-density lipoprotein cholesterol (HDL-C) metabolism,respectively and might increase the risk of coronary artery disease (CAD). It is becoming increasingly proven that polymorphisms in multiple genes are involved in the pathogenesis of CAD. Therefore, this study was conducted to investigate the association and interaction of MTHFR C677T, eNOS G894T, eNOS 4a4b and CETP TaqIB polymorphisms with the risk of CAD in multi-ethnics Malaysian population and the usefulness of random amplified polymorphic DNA (RAPD) analysis in discriminating CAD patients. A total of 344 subjects including angiographically confirmed 243 CAD patients and 101 control subjects were genotyped. The presence of MTHFR 677T allele was significantly associated with the increased risk of CAD and it was associated with higher total cholesterol and low-density lipoprotein cholesterol levels in the Chinese group. The presence of eNOS 4a allele was significantly associated with the increased risk of CAD in Malay and Indian groups. The CETP B2B2 genotype was significantly associated with higher HDL-C and associated with decreased risk of CAD in the Malay group. Moreover, the concomitant presence of MTHFR 677T and CETP B1 alleles was significantly increased the risk of CAD in Malay group and Chinese group but not Indian. At the same time, the concomitant presence of both CETP B1 and eNOS 4a alleles was significantly increased the risk of CAD in Malay group and Indian group but not Chinese. The RAPD analysis show that, under certain conditions, genetic polymorphisms in genomic DNA of CAD patients could be detected by using RAPD analysis and enable the discrimination of the CAD patients from the controls. In conclusion, this study shows that gene polymorphisms differ in both distributions and association with CAD among different ethnic groups in Malaysia. Moreover, this study has identified a novel ethnic-specific gene-gene interactions, suggested that the role of gene-gene interaction in the pathogenesis of CAD might be ethnic specific. The detected polymorphisms by the arbitrary primers OPO 02 and OPO 10 enable the discrimination of the CAD patients from the controls. These findings can be further analysed for biomarker development.